Commercial production of Florida pompano (Trachinotus carolinus) larvae at low salinity induces variable changes in whole-larvae microbial diversity, gene expression, and gill histopathology - Bradshaw, David J.; Perricone, Carlie S.; King, Laura E.; Allmon, Elizabeth B.; Sepúlveda, Maria; Riche, Marty; Wills, Paul S.; Kirchhoff, Nicole; Mejri, Sahar (Frontiers in Marine Science, 2023)
Introduction Salinity presents economic and technical challenges in land-based recirculating aquaculture systems (RAS) in the U.S. warm water marine finfish aquaculture industry. Many studies have shown euryhaline fish reared at salinities closer to their iso-osmotic salinity can yield enhanced production performance as well as potential reduced costs to farms. However, there is potential for osmotic stress in fish larvae to negatively impact larvae microbiome and innate immune system. Florida pompano (Trachinotus carolinus) is a popular sportfish has been targeted for land-based RAS due to its impressive market value and euryhaline capacity. This study investigated the impacts of rearing Florida pompano larvae at salinities closer to their iso-osmotic salinity. Materials and methods Larvae were cultured at 10, 20, and 30 ppt in triplicates, and larvae samples were collected for histopathology, microbiome, and whole transcriptomics analysis every three days from hatching until the time of weaning (24 days post hatch [DPH]). Water samples were also taken for microbiome analysis on every other larval sampling day. Discussion These changes were driven more by metamorphosis, causing an increase in expression of antioxidant genes (cat, gss, gsto1, and scara3) than by the presence of potentially pathogenic genera, which failed to induce an immune response (low or unchanged expression of downstream elements of the NOD1 or TLR5 pathways). These findings provide baseline information on Florida pompano low salinity tolerance in larviculture during early developmental stages. In addition, we have shown minimal effects on the immune system at salinities as low as 10 ppt. This work has important implications for larval health management and can be used to refine and direct future research regarding improving commercial production of warm water marine species